Potential of Ground and Unground Palm Oil Fuel Ash in Construction Material - Roslee, Faiza; Amani Filzah Mohd Kamil, Nor; Abd Kadir, Aeslina; Isia, Ismallianto; Ikhmal Haqeem Hassan, Mohd (International Journal of Engineering and Technology, 2018)
The uncontrolled bunches of palm oil fuel ash (POFA) leads environmental pollution and hazardous to the human. Besides, POFA can be classified as the high pozzolan matter. This feature attracts attention tremendous researchers to identify the usage of POFA to overcome the abundant issues. This paper is review about the reuse a POFA in a different method. The researcher found the potential by replaced the cement with POFA in construction material. In addition, findings shows that POFA can be use to reduce carbon content, loss of ignition and increased mineral oxide composition. Yet, POFA has good high potential and can be used in construction industriesÂ Â